Artificial intelligence and people management in the 21st century - Almeida, F.; Junça Silva, A.; Lopes, S. L. (Artificial intelligence in production engineering and management, 2024)
All facets of society have been transformed by the digital era, and human resources are no exception. Artificial Intelligence (AI), which has become more prevalent in people management, becomes a potent tool in this situation. AI enables businesses to evaluate massive amounts of data, spot trends, and reach conclusions using complex algorithms. These capa- bilities are giving businesses the tools they need to handle the human component and change how they operate (Santana & Díaz-Fernández, 2023). AI is becoming more prevalent in people management, having a huge impact and causing significant changes in how businesses manage their employees. The technological revolution has the power to funda- mentally alter how work is performed, with implications for employment, unemployment, performance, interpersonal interactions, and workplace emotions (Santhi & Muthuswamy, 2023). AI will be crucial in reorganiz- ing work organization and people management in the context of revolu- tion 4.0. AI’s potential to optimize and automate several processes in human resource management could lead to more precise and effective decision- making. AI can be used, for instance, to analyze resumes, find promising applicants, and perform virtual interviews in the recruiting and selection process (Huang et al., 2023). This speeds up the hiring procedure and increases the chance of discovering the talent that the company requires (Ore and Sposato, 2022). Concerns about the effects on employment are, however, also brought up by these changes. Some jobs may become obsolete as previously performed by humans, functions are automated, leading to structural unemployment (Brynjolfsson et al., 2017). On the other hand, AI also creates new job opportunities, especially in the area of developing and implementing AI technologies (Bughin, 2018). Organizations need to prepare for these changes by ensuring that workers have the necessary skills to adapt to an increasingly technological work environment. Aside from the influence on employment, AI can have an impact on workplace relationships and emotions. Interactions between coworkers and between workers and their supervisors may change if mundane jobs are automated and chatbots and virtual assistants are introduced (Calvaresi et al., 2023). While AI can help workers with feedback and advice, the lack of human interaction can hurt emotional well-being and job happi- ness (Ore and Sposato, 2022). As a result, it is critical to strike a balance between automation and human connection to maintain a healthy and productive work environment. AI will have a huge impact on people management and work organization as part of the 4.0 revolution (Asfahani, 2022). Organizations may utilize AI to collect massive amounts of data and use it to make educated decisions regarding recruitment, development, and performance management. Furthermore, AI can assist in identifying trends and patterns that might lead to increased productivity and efficiency at work. Predictive analytics and the application of advanced algorithms can also assist organizations in identifying hazards and taking proactive measures to avoid workplace difficulties (Faqihi and Miah, 2023). However, implementing AI in human resource management raises problems and ethical concerns. Data collection and analysis, for example, can raise issues about the privacy and security of employees’ information (Sakka et al., 2022). Furthermore, if algorithms and AI are not carefully built and managed, they can lead to bias and discrimination (Varsha, 2023). Organizations should be aware of these challenges and take steps to guarantee that AI implementation is ethical, transparent, and responsible. AI is changing human resource management, bringing significant changes to employment, interpersonal interactions, and workplace emo- tions. AI will play a critical role in redesigning people management and work organization as part of the 4.0 revolution (Chen, 2023). Organizations must be prepared to address the challenges and opportu- nities presented by AI, while also ensuring that deployment is done ethi- cally and responsibly, to maximize human potential in the workplace. This chapter aims to explore the importance and relevance of AI in people management, as well as to analyze its main applications and the associated ethical and social implications. We will address four key areas that are impacted by AI in people management: recruitment and selection, training, performance management, and the ethical and social implications of utilizing AI in people management. AI has played an important role in optimizing employment processes in the realm of recruitment and selection. Based on established criteria, AI systems may analyze CVs, appraise skills, and discover promising appli- cants. Furthermore, AI can be used to conduct virtual interviews, perhaps making the process more efficient and inclusive (Fulk et al., 2022). However, to minimize prejudice and injustice in the selection process, it is critical to address the limitations and algorithmic biases that may exist in such automated systems (Goretzko & Israel, 2021). In the context of training and talent development, AI provides new opportunities to identify skill gaps and tailor training programs to the needs of individual workers (Asfahani, 2022). AI can recommend custom- ized courses, workshops, and mentorships based on data analysis, to maxi- mize each worker’s professional growth. However, it is critical to ensure that the use of artificial intelligence in talent development does not replace human connection and the valorization of social and emotional abilities. Performance management is another area benefiting from AI. AI tools can collect data on workers’ performance, analyze key indicators, and pro- vide valuable insights to enhance individual and collective performance (França et al., 2023). In addition, AI can assist in identifying patterns of behavior that can positively or negatively affect the performance of indivi- duals and teams, allowing for the implementation of more effective cor- rective actions (Borges et al., 2021). However, it is necessary to ensure transparency and ethics in the use of these tools, avoiding excessive sur- veillance and manipulation of workers. It is essential to reflect on the ethi- cal and social implications of AI in people management. As AI becomes more present in decision-making on hiring, promotions, bonuses, and performance evaluation, concerns related to privacy, algorithmic discrimi- nation, and loss of employment arise (Khogali and Mekid, 2023). Responsible implementation of AI in people management requires adopt- ing ethical guidelines and considering its long-term societal impacts (Lefkowitz, 2021). In this chapter, we will address these issues by examining the impact of AI on recruitment and selection, training, and performance manage- ment, and its ethical and social implications. We will seek to identify the benefits and limitations of AI, as well as propose guidelines for the ethical and responsible use of this technology in people management.